Penyuluhan Kesehatan Ibu Hamil Cerdik Hadapi Pre Eklampsi dan Kecemasan - Pratiwi, Liliek; Gunawan, Ahmad Ade; Maharani, Aini Novita; Kusmayanti, Annissa Dwi; Rahmah, Atika; Wiyanto, Ayuni Rahma; Kamalin, Cleafatra Nurlaili; Aditia, Dimas; Lestari, Dini Ayu; Rochmah, Fahdzah Amalia; Tuzzaqroh, Fatimah; Qolbi, Fida Zauhair; Rosalia, Geulis Diah; Zuliyanti, Iklima; Nurbayani, Marta; Amalia, Mila; Putri, Nadya Restu; Maulidiyah, Nazwa; Hakimah, Nur Ba’iyyah; Fajri, Rafli Al; Roslinah, Roslinah; Alvaralisa, Rosmala Adawiyah; Maolana, Sandi; Fadhilah, Syahrul; Oktavia, Widia Shalva; Yuliyana, Yuliyana; Maharani, Yunita; Salsabila, Zahrha Ratna (Universitas Pahlawan Tuanku Tambusai, 2025)
Discovery and treatment of preeclampsia too late can be a life-threatening condition for both the mother and the child over the course of the pregnancy. Moreover, pregnancy-related anxiety might worsen the health of the mother and influence the baby's development. For this reason, it is imperative that expectant mothers be more ready to deal with these two problems by having the appropriate knowledge. By increasing awareness and encouraging prevention, this community service event was intended to inform expectant mothers about health concerns and help them to make more informed choices on how to control the risks of preeclampsia and anxiety. The event's informative lectures at the Village Hall were followed by casual conversations and a quiz based on the training material, which was utilized to hand out useful door prizes. The Sukasari Village Hall in Mandirancan, Kuningan District, provided the venue for all events. Participants had become more familiar about the signs of preeclampsia, how to regulate blood pressure, and basic relaxation techniques to lower anxiety following the assessment. Furthermore emphasized at the event was the essential part family support has in helping expected moms maintain their mental and physical health. Continuous instruction and an inclusive approach including all stakeholders should help to create a shared awareness of the need to recognize preeclampsia early and control stress throughout pregnancy. Translated using DeepL. com's free version.